Determinan yang Mempengaruhi Audit Delay: Studi Pada Perusahaan Terdaftar di Bursa Efek Indonesia - Mohammad Khoirul Anam (Department of Accounting-Faculty of Economic and Business (FEB), 2017)
Audit delay is an important issue because it can impact on the timeliness of the delivery of accounting information, which further affects the relevance of accounting information. The purpose of this study is to analyze the factors that affect audit delay. Analytical technique used is logistic regression. From the analysis of logistic regression can be concluded that, for industry sector variables shows that 5 industry sectors give influence and 4 industry sectors have no effect. For Reputation and Probability variables have a significant effect. Medium variable size of the company has no significant effect. There is a simultaneous and significant influence of Industry Type variables, Firm Reputation, Profitability and Company Size to Audit Delay.